2021
DOI: 10.3390/brainsci11050658
|View full text |Cite
|
Sign up to set email alerts
|

The Participation of Microglia in Neurogenesis: A Review

Abstract: Adult neurogenesis was one of the most important discoveries of the last century, helping us to better understand brain function. Researchers recently discovered that microglia play an important role in this process. However, various questions remain concerning where, at what stage, and what types of microglia participate. In this review, we demonstrate that certain pools of microglia are determinant cells in different phases of the generation of new neurons. This sheds light on how cells cooperate in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 102 publications
1
23
0
Order By: Relevance
“…Recent studies have indicated the role of neuron-microglia interaction in the function and maturation of glutamatergic synapse and demonstrated how microglia influence synaptic organizations and activity [111,112]. Moreover, Perez-Rodriguez described the role of microglia in neurogenesis in the adult brain [113]. Despite all studies, the physiological function of microglial cells and their interplay with neurons in the brain is not fully elucidated.…”
Section: Glutamatergic Signaling In Microglia-neuron Communication In Admentioning
confidence: 99%
“…Recent studies have indicated the role of neuron-microglia interaction in the function and maturation of glutamatergic synapse and demonstrated how microglia influence synaptic organizations and activity [111,112]. Moreover, Perez-Rodriguez described the role of microglia in neurogenesis in the adult brain [113]. Despite all studies, the physiological function of microglial cells and their interplay with neurons in the brain is not fully elucidated.…”
Section: Glutamatergic Signaling In Microglia-neuron Communication In Admentioning
confidence: 99%
“…Microglia, known as “brain gardeners,” have been found to influence neuronal proliferation, differentiation, and maturation [ 65 , 66 , 67 ]. Microglial morphology is closely linked to microglial functions [ 68 , 69 ], and changes in microglial phenotype are related to the impairment of hippocampal neurogenesis under pathological conditions [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microglia are macrophage-like cells in the CNS that have the function of maintaining homeostasis under physiological conditions. , Sensitization of microglia is a vital part of the pathogenesis of inflammatory pain. Tissue injury activates microglia, which secretes a variety of pro-inflammatory cytokines, such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor (TNF-α). , The discharge of these pro-inflammatory cytokines promotes the persistence of behavioral hypersensitivity reactions after injury or surrounding inflammation and plays an influential role in chronic inflammatory pain . In the spinal cord ischemia–reperfusion model, the increased expression of the chemokine C-X-C motif ligand 10 (CXCL10) led to overexpression of the chemokine receptor C-X-C motif receptor 3 (CXCR3) and stimulated the sensitization of microglia and the release of pro-inflammatory cytokines, eventually enlarging the inflammatory cascade and pain process .…”
Section: Glial Cells In the Central Nervous System And Inflammatory Painmentioning
confidence: 99%